Tracing the origins of Malaysia - Darshan Singh, Ranjit Singh (Sunday Star, 2013)

(untitled)
THE famous announcement on May 27,1961 by Tunku Abdul Rahman, then the Prime Minister of the Federation of Malaya, calling for forging closer political and economic cooperation between Malaya,Singapore,North Borneo,Brunei and Sarawak,is generally taken as the starting point for the formation of Malaysia on Sept 16,1963. The roots of the Malaysia scheme, however, go further back in time and were embedded in British plans hatched in 1942 for the decolonisation of South-East Asia in the post-Second World War period.